Student’s digital competences in Belgium and Romania: A comparative analysis - Vodă, Ana Iolanda; Gradinaru, Camelia; Cautisanu, Cristina; Poleac, Gabriela (Frontiers in Education, 2022)
This research explores students’ digital competences level in three major universities from Belgium and Romania, based on a combination of seven core skills: communication and collaboration skills, creativity skills, critical thinking skills, information skills, problem-solving skills and technological skills. We applied a quantitative design based on an online survey, applied during March 2021-May 2022 using Confirmatory Factor Analysis. The study focuses on examining the qualifications and implementation of students’ digital abilities in Romania and Belgium, looking for commonalities and discrepancies. The results indicate that students from Belgium have higher average scores for communication and collaboration, information, and problem-solving digital skills, while, in the case of students from Romania, creativity and technological skills have the highest average scores. In addition, there were not found significant differences between countries regarding the average scores of critical thinking digital skills. Although having a basic understanding of digital competences is advised, improved policies are required to promote the development of these skills as the skill sets needed for information and communication technology employees are more demanding.